Exploration students' computational thinking skills in mathematical problem solving based on field independent and dependent cognitive style - Suryanti, Lilis; Masduki, Masduki (Desimal: Jurnal Matematika, 2024)
Computational thinking skills play an important role in helping students solve mathematical problems. Students' problem-solving ability is influenced by cognitive style. The purpose of this study was to explore the computational thinking ability of prospective mathematics teachers based on field-independent and field-dependent cognitive styles. This research uses a qualitative approach with a case study design. Data collection instruments used are test questions, cognitive style questionnaires, and interview guidelines. Before use, the test questions were validated by two mathematics education experts and tested on five prospective mathematics teacher students. The subjects of this study were 47 prospective math teacher students at one of the private universities in Surakarta. Based on the test results and cognitive style questionnaire, researchers selected 3 field independent students and 2 field dependent students to be interviewed. The results showed that at the abstraction stage, all subjects can represent mathematical concepts in symbols or mathematical language appropriately. While at the stage of thinking algorithms and generalization, subjects with a field-dependent style tend to give answers that are less precise. Thus, it can be concluded that there are differences in the ability in the computational thinking process of students based on cognitive style.